The Relationship Between Reader and Writer in Contemporary Haiku Poems (Papers in Arts and Humanities, 2025)
The purpose of this paper is to look at the relationship of communication and readers’ participation in contemporary haiku poems. The poems selected for exemplification in this paper will be from Haiku Canada Members’ Anthology 2024. No Two Alike. The way in which readers work their way through meaning will be underlined, through free associations and use of universal symbols, and also based on common life experiences. A reader response approach will be adopted, since it has in view the way readers react to any text. Textual analysis will be combined with the readers’ emotional reactions and interpretations based on personal life experiences and cultural background. We can speak of communities of readers, in this case made up by the Western culture writers of an originally Japanese poem, the haiku. It is adapted and also compatible with other cultural mindsets. The way readers are engaged in the haiku poetry experience further leads to haiku being used in therapy, to encourage patients to express themselves, and become aware of their emotions, without thinking about the rules of this type of poem.
Keywords: reader response; mindfulness; present; free associations; dialogue